ANALISIS PANGSA PASAR DENGAN METODE BCG MATRIKS PADA KOPERASI SIMPAN PINJAM MAKMUR MANDIRI CABANG PURWOKERTO - Muhamad Ardaf Ramadhani; Agestiana Anti Mukharomah; Gigih Esa Pangestu; Yoiz Shofwa Shafrani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to evaluate the market share position of various savings and loan products offered by the Makmur Mandiri Savings and Loan Cooperative, Purwokerto Branch using the Boston Consulting Group (BCG) Matrix approach. The BCG Matrix was chosen because of its ability to classify products based on two main aspects, namely relative market share and market growth rate. The data analyzed came from financial reports and the volume of cooperative transactions during the period 2020 to 2022. The results of the analysis show that the Employee Loan product is in the Star quadrant, Voluntary Savings is included in the Cash Cow quadrant, while Digital Services and MSME Assistance are included in the Question Mark quadrant. Meanwhile, Social Funds are included in the Dog quadrant. Each product category requires a different management strategy. These findings provide strategic input for cooperative managers in formulating the direction of product development and allocating resources optimally to encourage sustainable cooperative growth.